Breast Cancer: Neoadjuvant Chemotherapy - Barbara F. Shea; Martha C. Monroe (EDIS)
FCS8827, a 4–page fact sheet by Barbara Shea and Martha Monroe, explains the process of "neoadjuvant" (pre-surgery) chemotherapy for breast cancer and describes its advantages and disadvantages. This publication will be useful to patients who are trying to decide whether to have surgery right away or begin their treatment with chemotherapy. Published by the UF Department of Family, Youth and Community Sciences, February 2007.